Role of fibronectin and IOL surface modification in IOL: Lens capsule interactions. (August 2022) - Jaitli, Arjun; Roy, Joyita; Chatila, Amjad; Liao, Jun; Tang, Liping
Abstract: Posterior Capsule Opacification (PCO) is one of the most common complications of cataract surgery. While studies have shown that IOL material properties and fibronectin adsorption may affect IOL-induced PCO in the clinical setting, the mechanism governing such interactions is not totally understood. Since strong adhesion forces between IOLs and posterior capsules (PCs) have been shown to impede cell infiltration and thus reduce PCO formation, this study was designed to assess whether fibronectin adsorption and IOL material properties would impact the IOL:PC adhesion force and cell infiltration using a PCO predictive in vitro model and a macromolecular dye imaging model, respectively. Our results showed that fibronectin adsorption significantly increased the adhesion forces and reduced simulated cell infiltration between acrylic foldable IOLs and the PC at physiological temperature in comparison to fibronectin-free controls. This fibronectin-mediated strong IOL: PC bond may be contributing to low PCO rates in the clinic for acrylic foldable IOLs. In addition, acrylic foldable IOLs coated with Di(ethylene glycol) (Diglyme), a hydrophilic coating known to reduce protein adsorption, was tested for its ability to alter adhesion force and cell infiltration. We observed that IOLs coated with Diglyme coating greatly reduced surface hydrophobicity and fibronectin adsorption of acrylic foldable IOLs. Furthermore, Diglyme coated IOLs showed significantly reduced adhesion force and increased simulated cell infiltration at the IOL:PC interface. The overall results support the hypothesis that IOL surface properties and their ability to adsorb fibronectin may have great impact on the IOL:PC adhesion force. A tight binding between IOLs and PC may contribute to the reduction of cell infiltration and thus the PCO incidence rate in the clinic. Highlights: Fibronectin adsorption and IOL material properties would impact IOL: posterior capsule (PC) adhesion force and cell infiltration. Fibronectin adsorption increased the adhesion forces and reduced cell infiltration between acrylic foldable IOLs and PC. Fibronectin adsorption does not influence the IOL:PC adhesion forces and cell infiltration in PMMA and silicone IOLs. Diglyme-coated IOLs possessed lessened adhesion force and increased cell infiltration at IOL:PC interface. A tight binding between IOL and PC may contribute to the reduction of cell infiltration and thus PCO incidence rate.